Rancang Bangun Media Pemasaran Rumah Berbasis Web Dengan Studi Kasus Pada Perumahan Espana Makassar : Rancang Bangun Media Pemasaran Rumah Berbasis Web Dengan Studi Kasus Pada Perumahan Espana Makassar - Zaman, Baizul (Jurnal INSYPRO (Information System and Processing), 2022)
In this study, the authors built a web-based home marketing system. In this website the image of the house is presented in a 360 degree form. This is done as an effort to provide convenience to prospective customers in seeing the shape of the house that is being marketed. This website is built using visual studio code and xampp as the manager of the database. The results of this study showed that the use of websites as a marketing medium managed to increase the number of visits of prospective home buyers in Espana Makassar housing by 85%.